The importance of nasoendoscopic findings & Muller's maneuver in predicting severity of obstructive sleep apnoea - Mohamed, Ahmad Khairi (2020)
Objectives: To determine the association between deviated nasal septum (DNS), inferior turbinate hypertrophy (ITH) and upper airway obstruction during Muller’s maneuver (MM) with severity of obstructive sleep apnoea (OSA). Methods: A cross sectional study involving patients with OSA. All consented patients who fulfilled the criteria underwent upper airway examination using rigid 0-degree endoscope and flexible nasopharyngolaryngoscope (FNPLS) for MM, focusing on the anatomy of inferior turbinate and nasal septum as well as the airway obstruction at retropalatal and retroglossal levels. Mladina classification of DNS was used. Sociodemographic data and clinical characteristic for inferior turbinate, nasal septum and upper airway obstruction were recorded and analyzed using Statistical Package for Social Sciences (SPSS). Results: A total of 64 OSA patients aged between 23 to 60 years (31 male and 33 female) involved. The average age was 40.8 ± 8.8 years and the mean BMI was 29.7 ± sd 2.9. The association between DNS and severity of OSA, also between MM findings with severity of OSA were highly significant with p-value <0.001. However, ITH did not show a significant association with severity of OSA (p- value >0.05). Conclusion: Overall, DNS based on Mladina classification and upper airway obstruction during MM are significant in predicting severity of OSA.